Research progress on the resistance of foodborne Listeria monocytogenes to quaternary ammonium disinfectants and its prevention and control strategies - WANG Zhenhua; LI Gang; ZHANG Min; WANG Yeru (Zhongguo shipin weisheng zazhi, 2023)
Listeria monocytogenes （L. monocytogens） is a common foodborne pathogen that can become a potential source of food contamination by forming single or multi-species biofilms through population induction on the surface of stainless steel of food processing equipment. Quaternary disinfectants are commonly used for cleaning and disinfection of processing equipment surfaces in food plant， while L. monocytogenes biofilms are tolerant to it through various mechanisms， such as active efflux pump system， stress response and gene regulation. In this paper， the formation and tolerance mechanisms of L. monocytogenes biofilms are reviewed， and the applications of physical disinfection and new combined disinfection technologies for foodborne L. monocytogenes prevention and control in recent years are summarized to provide ideas for the development of new and efficient disinfection technology， as well as to supply important references for enterprises to establish the control measures for L. monocytogenes and other microbial.